Are more equal societies happier? Subjective well-being, income inequality, and redistribution - Tamás Hajdu; Gábor Hajdu (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
Using four waves of the European Social Survey, we analyze the association of income inequality and redistribution with subjective well-being. Our results provide evidence that people in Europe are negatively affected by income inequality, while reduction of inequality has a positive effect on well-being. Since we simultaneously estimate the effects of inequality and its reduction, our results indicate that not only the perceived income inequality what influences subjective well-being, but also the process, the extent of redistribution, what lead to that state. These impacts are different in Eastern and Western Europe. Inequality aversion and the positive effect of redistribution seem to be stronger also for less affluent members of the societies and left-wing oriented individuals.
Keywords: D63; I31; 330; subjective well-being; satisfaction; income inequality; redistribution